Comparison of Hemodynamic Response after Pneumoperitoneum with Versus without Pre-Emptive Magnesium Sulphate in Patients Undergoing Laparoscopic Cholecystectomy - Tooba Shafiq, Maham Afzal Rana, Afshan Nisar, Hina, Muhammad Athif Akram (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the hemodynamic response after pneumoperitoneum with versus without pre-emptive magnesium sulphate in patients undergoing laparoscopic cholecystectomy. Study Design: It was a randomized controlled trial Setting: Research was conducted at Department of Anesthesiology Lahore General Hospital, Lahore. Materials and Methods: This study involved 104 patients of both genders aged between 18-70 years undergoing laparoscopic cholecystectomy which were randomly divided into two treatment groups. Patients in Group-A received pre-emptive magnesium sulphate while patients in Group-B were received normal saline as placebo. Outcome variable was hemodynamic response to pneumoperitoneum. It was assessed in terms of mean heart rate, mean diastolic and systolic blood pressure after 30 minutes of pneumoperitoneum which were measured and compared between the two groups. Results: The mean age of the patients was 44.8±9.2 years while the mean BMI was 25.3±2.7 Kg/m2. There were 31 (29.8%) male and 73 (70.2%) female patients with a male to female ratio of 1:2.4. 63 (60.6%) patients belonged to ASA Class-I while 41 (39.4%) patients belonged to ASA Class-II. The mean heart rate (80.8±4.5 vs. 87.7±5.0 bpm; p-value<0.001), mean diastolic BP (77.6±6.7 vs. 84.9±6.0 mmHg; p-value<0.001) and mean systolic BP (133.3±8.2 vs. 140.6±8.9 mmHg; p-value<0.001) were significantly lower after 30 minutes of pneumoperitoneum in patients receiving magnesium sulphate as compared to normal saline. Conclusion: Pre-emptive magnesium sulphate attenuated the hemodynamic response of pneumoperitoneum evident from significantly lower mean heart rate and means diastolic and systolic blood pressure after 30 minutes of pneumoperitoneum as compared to controls which advocate its preferred use in future practice.